2008
DOI: 10.1016/j.bbcan.2007.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Proteases as modulators of tumor–stromal interaction: Primary tumors to bone metastases

Abstract: SummaryAs cells undergo oncogenic transformation and as transformed cells arrive at metastatic sites, a complex interplay occurs with the surrounding stroma. This dialogue between tumor and stroma ultimately dictates the success of the tumor cells in the given microenvironment. As a result, understanding the molecular mechanisms at work is important for developing new therapeutic modalities. Proteases are major players in the interaction between tumor and stroma. This review will focus on the role of proteases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 72 publications
4
53
0
1
Order By: Relevance
“…Targeting CCL2 with a neutralizing antibody caused prostate tumor regression (24)(25)(26). The list also includes mRNAs encoding the matrix metalloproteinases (MMPs) MMP3 and MMP9, which are overexpressed in PC3 prostate cancer cells (27), and promote invasion and metastasis by rearrangement of the ECM (28,29). Other mRNAs encode the inhibitor of apoptosis, baculoviral IAP repeat-containing protein 2 (BIRC2), and the growth factor VEGFC.…”
Section: Resultsmentioning
confidence: 99%
“…Targeting CCL2 with a neutralizing antibody caused prostate tumor regression (24)(25)(26). The list also includes mRNAs encoding the matrix metalloproteinases (MMPs) MMP3 and MMP9, which are overexpressed in PC3 prostate cancer cells (27), and promote invasion and metastasis by rearrangement of the ECM (28,29). Other mRNAs encode the inhibitor of apoptosis, baculoviral IAP repeat-containing protein 2 (BIRC2), and the growth factor VEGFC.…”
Section: Resultsmentioning
confidence: 99%
“…MMP-9 act not only as solubilizers of bone matrix but also as regulators of the initiation of bone resorption [8]. Study has shown that MMP-9 is produced by osteoclast in the human bone tissues and suggest that it can degrade bone collagens in concert with MMP-1 and cysteine proteinases in the subosteoclastic microenvironment [16]. Several studies have been conducted to analyze the MMP-9 expression in ameloblastoma [8,[12][13][14][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Although high protease activities are found in many solid tumors, 37 the use of a stringent assay of calpastatin degradation and the limiting of our analysis to HCCs arising on noncirrhotic livers allowed us to correlate calpain activation with a Bid decrease in human HCC. Although more clinical samples need to be analyzed to substantiate our interpretation, these data are consistent with the idea that the activation of calpains by HCV and its consequences on the apoptotic signaling pathways, observed in several animal and cellular models, are also relevant to human pathology.…”
Section: Discussionmentioning
confidence: 99%